An optimal circular antenna array design considering the mutual coupling employing ant lion optimization. Issue 2 (9th March 2021) - Das, Avishek; Mandal, Durbadal; Kar, Rajib
Abstract: This paper presents an efficient approach for the design of a non-uniform single ring circular antenna array (CAA) for the synthesis of the optimal far-field radiation pattern. A recently proposed meta-heuristic-based optimization technique known as ant lion optimization (ALO) is applied in this paper to determine the optimum set of current amplitude excitation weights and the inter-element distance among the array elements to reduce the side lobe level (SLL) and 3-dB beam width considering the mutual coupling effect. The results achieved by employing the ALO algorithm are compared with the uniform radiation pattern and with those of the recently reported literature containing equal sets of elements to prove the superiority of ALO algorithm. Three different design examples of 8, 10, and 12 elements CAA are presented, and their performances are compared to illustrate the capability of the ALO algorithm-based approach over those of the recently reported literature.